Peran Media Digital dalam Pembelajaran Bahasa Indonesia: Dimensi Kognitif, Emosional, dan Perilaku - Yuliarti, Yuliarti; Riansi, Erwin Salpa; Sultoni, Achmad (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
This study investigates the role of digital media in enhancing student engagement and learning in Indonesian language education. The research aims to analyze the impact of digital media on three dimensions of engagement: cognitive, emotional, and behavioral. A mixed-method approach was employed, involving surveys of 300 high school students and in-depth interviews as well as classroom observations with 10 Indonesian language teachers from various institutions. Quantitative data revealed a significant increase in student engagement, with average scores of 85% for cognitive, 78% for emotional, and 82% for behavioral engagement after the implementation of digital media. Qualitative analysis supports these findings, highlighting interactive features such as gamification, multimedia resources, and collaborative platforms as key factors driving student engagement. Digital media not only enhances deeper cognitive processing and emotional connections but also facilitates active participation in learning activities. This study underscores the importance of teacher training and institutional support to optimize the use of digital media, thereby creating more dynamic and effective learning experiences in Indonesian language education.